Molecular identification of Plasmodium species in symptomatic children of Democratic Republic of Congo - Hugo Kavunga-Membo; Gillon Ilombe; Justin Masumu; Junior Matangila; Joël Imponge; Emile Manzambi; Francis Wastenga; Dieudonné Mumba Ngoyi; Jean-Pierre Van Geetruyden; Jean Jacques Muyembe (Malaria Journal, 2018)
Abstract Background Worldwide, the highest malaria mortality is due to Plasmodium falciparum infection. However, other species of Plasmodium (Plasmodium vivax, Plasmodium ovale, Plasmodium malariae, and Plasmodium knowlesi) can also cause malaria. Therefore, accurate identification of malaria species is crucial for patient management and epidemiological surveillance. This study aimed to determine the different Plasmodium species causing malaria in children under 5 years old in two provinces (Kinshasa and North Kivu) of the Democratic Republic of Congo (DRC). Methods From October to December 2015, a health-facility based cross-sectional study was conducted in General Reference Hospitals in Kinshasa and North Kivu. Four hundred and seven blood samples were collected from febrile children aged ≤ 5 years. Nested polymerase chain reaction assays were performed for Plasmodium species identification. Results Out of 407 children, 142 (34.9%) were infected with Plasmodium spp. and P. falciparum was the most prevalent species (99.2%). Among those infected children, 124 had a mono infection with P. falciparum and one with P. malariae. Mixed infections with P. falciparum/P. malariae and P. falciparum/P. vivax were observed in 6 (1.5%) and 8 (2.0%) children, respectively. The prevalence of infection was higher in females (64.8%) than in males (35.2%), p < 0.001. The age-specific distribution of infection showed that children of less than 2 years old were less infected (18.4%) compared to those aged above 2 years (81.6%), p < 0.001. Conclusion Although this study showed clearly that the most prevalent species identified was P. falciparum, the findings demonstrate the existence of non-falciparum malaria, especially P. malariae and P. vivax among children aged ≤ 5 years living both Kinshasa and North Kivu Provinces in DRC.